2019
DOI: 10.1109/access.2019.2920094
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Bidirectional Controlled Teleportation by Using Nine-Qubit Entangled State in Noisy Environment

Abstract: In this paper, a novel protocol for asymmetric bidirectional controlled quantum teleportation (ABCQT) by using the nine-qubit entangled state as a quantum channel is proposed. Alice transmits an arbitrary three-qubit entangled state to Bob and at the same time, Bob transmits an arbitrary single-qubit entangled state to Alice under the permission of a third party as a controller. This protocol is based on the Hadamard (H) gates, controlled-not (CNOT) operations, appropriate unitary operations, and single-qubit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…The energy dissipation is a consequence of interaction of quantum system with an amplitude damping channel. In simple terms, a quantum system gaining or loosing energy from or to its environment is described as change in its amplitude or amplitude damping 38,39 probability of gain or loss of amplitude or decoherence rate; the Kraus operators of amplitude damping channel can be described as follows (Eq. 27),…”
Section: A Amplitude Dampingmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy dissipation is a consequence of interaction of quantum system with an amplitude damping channel. In simple terms, a quantum system gaining or loosing energy from or to its environment is described as change in its amplitude or amplitude damping 38,39 probability of gain or loss of amplitude or decoherence rate; the Kraus operators of amplitude damping channel can be described as follows (Eq. 27),…”
Section: A Amplitude Dampingmentioning
confidence: 99%
“…Bitflip noise is characterised by random bitflip errors 38 with probability 0 ≤ κ B ≤ 1 (say for 0) while the other probability will be 1 − κ B (say for 1). Thus, the Kraus operators of bitflip noise channel can be described as Eq.…”
Section: B Bitflip Noisementioning
confidence: 99%
See 2 more Smart Citations
“…In 1993, Bennett et al [13] first proposed quantum teleportation with a Bell pair, which was later demonstrated in an experiment by Bouwmeester et al [14]. Quantum teleportation has been developed rapidly both theoretically [15]- [26] and experimentally [14], [27]- [33]. To satisfy a variety of different quantum communication scenarios, a series of protocols for quantum teleportation have been proposed involving different quantum channels such as Bell states [15]- [18], GHZ states [19], [20], W states [21]- [23], etc.…”
Section: Introductionmentioning
confidence: 99%